2005
DOI: 10.1186/1471-2431-5-22
|View full text |Cite
|
Sign up to set email alerts
|

Variations in rates of nosocomial infection among Canadian neonatal intensive care units may be practice-related

Abstract: BackgroundNosocomial infection (NI), particularly with positive blood or cerebrospinal fluid bacterial cultures, is a major cause of morbidity in neonatal intensive care units (NICUs). Rates of NI appear to vary substantially between NICUs. The aim of this study was to determine risk factors for NI, as well as the risk-adjusted variations in NI rates among Canadian NICUs.MethodsFrom January 1996 to October 1997, data on demographics, intervention, illness severity and NI rates were submitted from 17 Canadian N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 19 publications
5
53
1
3
Order By: Relevance
“…These findings are consistent with the results of previous larger studies of late-onset sepsis in VLBW infants (3,10,31) that demonstrated CONS in 14 to 23% of patients and S. aureus in 1.6 to 5% of patients. The majority (63%) of sepsis cases caused by CONS in this study were confirmed by two or more peripheral blood cultures growing CONS.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are consistent with the results of previous larger studies of late-onset sepsis in VLBW infants (3,10,31) that demonstrated CONS in 14 to 23% of patients and S. aureus in 1.6 to 5% of patients. The majority (63%) of sepsis cases caused by CONS in this study were confirmed by two or more peripheral blood cultures growing CONS.…”
Section: Discussionsupporting
confidence: 83%
“…The mortality rates in patients with a diagnosis of NI in the NICU was reported to be 17% in a multi-center study performed in Europe between 1996 and 1997 and 10.3% in Japan in the years between 2002 and 2003 (2.1% in patients without NI) (31,33). In a study performed in Canada in 1996-1997, the mortality rate was found to be markedly higher in patients with a diagnosis of NI (8.5%) compared to the patients without a diagnosis of NI (1.3%) among patients with a birth weight of >1500 g in the NICU, but the mortality rates were found to be 8.7% and 8.6% in patients with and without NI, respectively among patients with a birth weight of <1500 g (20). In a study performed in Germany, the mortality rate was found to be 8.1% in the patients hospitalized in the NICU; when classified according to birth weight, the mortality rate was found to be 15,2% in patients with a birth weight of <1000 g and 2,8% in patients with a birth weight of 1000-1499 (23).…”
Section: Mortality Ratementioning
confidence: 92%
“…In a study performed in 2002 in Italy, the rate of NI was reported to be 48% in infants with a birth weight of <1500 g (21). In Canada, the frequency of NI was found to range between 6.7% and 74.5% in infants with a very low birth weight and between 0.1% and 17% in infants with high birth weight in the NICU between the years of 1996 and 1997 (20). In a surveillance study performed in Germany between the years of 1994 and 1995, 61% of NIs were found to develop in patients with a birth weight of <1500 g (34).…”
Section: Nis By Birth Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Traditionally, prevention of EONS has focused on prevention of vertical transmission of group B Streptococcus (GBS or Streptococcus agalactiae) through administration of maternal intrapartum antibiotic prophylaxis. 5 No effective strategies are currently available to prevent EONS caused by other organisms, 6 such as Escherichia coli. 7 Several recent studies of patient populations in the US have reported a change in neonatal infection patterns, with a reduction in EONS caused by GBS but an increase in EONS caused by ampicillin-resistant E. coli.…”
Section: Introductionmentioning
confidence: 99%